2010
DOI: 10.1590/s0103-50532010001100004
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic application of selenium and tellurium compounds as glutathione peroxidase enzyme mimetics

Abstract: A glutationa peroxidase (GPx) é uma importante enzima que faz parte do sistema de defesa do organismo frente a substâncias nocivas formadas durante o metabolismo do oxigênio, como peróxidos e seus derivados. Diversas estratégias para desenvolver novos miméticos, assim como para aumentar a atividade mimética da GPx em compostos como disselenetos, selenetos e teluretos, vêm sendo propostas nos últimos anos. Nesta revisão é apresentado um balanço, dos últimos dez anos, referente ao desenvolvimento e à avaliação d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(32 citation statements)
references
References 30 publications
(47 reference statements)
0
30
0
1
Order By: Relevance
“…Several laboratories have reported the synthesis and characterisation of novel small selenium compounds as functional mimics of GPx, either by modifying the basic structure of ebselen or by incorporating some structural features of the native enzyme (Alberto et al 2010;Back 2009;Bhabak & Mugesh 2010). These synthetic mimics can be classified into three major categories: (i) cyclic selenenyl amides having a Se-N bond, (ii) diaryl diselenides, and (iii) aromatic or aliphatic monoselenides (Bhabak & Mugesh 2010).…”
Section: Novel Gpx1-mimeticsmentioning
confidence: 99%
“…Several laboratories have reported the synthesis and characterisation of novel small selenium compounds as functional mimics of GPx, either by modifying the basic structure of ebselen or by incorporating some structural features of the native enzyme (Alberto et al 2010;Back 2009;Bhabak & Mugesh 2010). These synthetic mimics can be classified into three major categories: (i) cyclic selenenyl amides having a Se-N bond, (ii) diaryl diselenides, and (iii) aromatic or aliphatic monoselenides (Bhabak & Mugesh 2010).…”
Section: Novel Gpx1-mimeticsmentioning
confidence: 99%
“…Numerous organochalcogen compounds containing amine, peptide/amide and carbamate groups enhances the rates of their redox reactions 16,22,23,47 and the effect of these groups on the activity of organotellurium compounds was expected to be more pronounced than that of corresponding organoselenium compounds. 47,23 The biological activity of chiral organochalcogen compounds may be specific.…”
Section: Introductionmentioning
confidence: 99%
“…47,23 The biological activity of chiral organochalcogen compounds may be specific. Recently reported that the organoselenium and tellurium compounds which contain the secondary interactions between chalcogen atom and other heteroatoms [TeX, X = N, O, S, Cl, Br, I] through internal chelation play an important role in the catalytic antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several types of these compounds play a crucial role in biology and biochemistry. For instance, they have been used as antioxidants and apoptosis inducers, and their role in the degradation of hydroperoxides and in the chemoprevention of cancer in a variety of organs has been exploited [7,8].…”
Section: Introductionmentioning
confidence: 99%